Hydraulics of groundwater - Bear, Jacob (Dover Publications, 2007)
This text explores the laws and equations governing the flow and storage of groundwater in aquifers. It provides groundwater hydrologists — as well as engineers and planners dealing with the development and management of groundwater resources — with all the necessary tools to forecast the behavior of a regional aquifer system. 1979 edition.